DESIGNING A WEB-BASED ACHIEVEMENT MANAGEMENT INFORMATION SYSTEM - Hartatik Hartatik; Suci Wulandari; Mega Suci W (International Journal of Multidisciplinary Research and Literature, 2023)
The development of technology is increasingly advanced, and increasingly entering the digital era, everything we need is made easier with technology. One is in the achievement management of each student by using the achievement management information system. This information system uses a development research method consisting of analysis, design, flow and factor design, implementation (coding) and trials. The purpose of creating this information system is to design and build an achievement management information system at SMA Negeri 1 Wonosari Klaten. This system begins with analyzing system needs, creating business processes, designing ERD, making system designs, and designing user interfaces. In conducting the test, this system uses the BlackBox method. The result of this system is that it runs well and corresponds to its functionality